Driven by the markets? ECB sovereign bond purchases and the securities markets programme - Ansgar Belke (Intereconomics, 2010)
At the height of the European sovereign debt crisis, the European Central Bank decided to purchase distressed European government bonds. Even worse, and more importantly, the ECB is providing direct support of several hundred billions of euros to troubled banks via its normal monetary policy operations by granting them the opportunity to refinance at an interest rate of 1%. This article argues that these purchases will result in common monetary policy being dominated by national fiscal policies. The most worrisome aspect is that the euro area appears to have stumbled into unconventional monetary policies that, once started, will be difficult to exit. In the euro area, properly functioning financial markets are at risk.
Keywords: 330